EL CARIOTIPO DE CHAETANTHERA PENTACAENOIDES (PHIL.) HAUMAN (ASTERACEAE) - Baeza, Carlos M.; Torres-Díaz, Cristián (Gayana Botánica, 2006)
The karyotype of Chaetanthera pentacaenoides (Phil.) Hauman from Chile was examined. This species belong to the subgenus Egania. The species has 2n = 2x = 20 chromosomes, with 8m + 2sm chromosomes. The reported karyotype is symmetric (AsI % = 58.73).